The assessment of the fetal heart function using two-dimensional speckle tracking with a high frame rate. (December 2020) - Ohira, Akiko; Hayata, Kei; Mishima, Sakurako; Tani, Kazumasa; Maki, Jota; Mitsui, Takashi; Eto, Eriko; Masuyama, Hisashi
Abstract: Background: Two-dimensional (2D) speckle tracking echography (STE) is a new diagnostic modality that allows for the assessment of myocardial deformation. The present study assessed the feasibility of fetal 2D-STE at a high frame rate and determined the reference values for left ventricular (LV)- and right ventricular (RV)- global longitudinal strain (GLS). Methods: In this prospective study, 109 fetuses with gestational ages ranging from 18 to 38 weeks underwent 2D echocardiography between August 2018 and December 2019. All recordings were performed using the Aplio i800 (CANON Medical Systems Corporation, Tochigi, Japan) and a convex probe (4 MHz) for fetuses. Results: Longitudinal peak systolic strain measurements were obtained in 98 of 109 healthy fetuses (90%). All ultrasound videos were recorded with a median frame rate of 172 (range, 100–274) frames/s. The LV-GLS was almost constant, regardless of the number of weeks since the second trimester ( r  = −0.0087, p  = ns). The RV-GLS decreased significantly with gestational age ( r  = 0.39, p  < 0.01). Conclusions: STE may be useful for quantifying the systolic myocardial function in a fetus. Highlights: Two-dimensional speckle tracking echography may be feasible in a fetus. This report uses a high frame rate, with STE conducted in a large population. The right ventricular GLS decreased significantly with gestational age.